An overview of recent developments in theory and practice - de Haan, Jakob (Henry Stewart Talks, 2009)
Markets for government debt securities, Objectives of debt management: theory and practice, The organization of debt management, Maturity of debt, Inflation-indexed debt, Currency denomination of debt, Ownership of debt, Issuing and trading practices